Problem Pemilihan Kampus Swasta Di Kalangan Generasi Z Dengan Pendekatan Model Marketing AIDA+S - Ambardi, Ambardi; Pribadi, Rizky Maulana; Aminah, Aam; Efriadi, Adi Rizfal (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to explore the application of the AIDA+S marketing model in the marketing strategies of private universities for recruiting prospective Generation Z students to choose a campus. Methods: The type of research to be used is quantitative, associative, and descriptive. The population in this study consisted of all students actively studying at the Ahmad Dahlan Institute of Technology and Business. The sampling procedure employed in this study was non-probability, utilizing a purposive sampling technique, with a sample size of 150 respondents. The data analysis used was multiple linear regression analysis to determine the influence of several AIDA+S variables on the Decision variable of choosing a campus. Results: The results of this study concluded that the AIDA+S Model had a significant effect on the Decision to choose a campus. Furthermore, for the variables attention, interest, and desire do not have a substantial impact on the decision to select a campus among Generation Z. While for the variables action and satisfaction, there is a considerable influence on the decision to select a campus among Generation Z. The biggest reason respondents choose a campus because it is close to home according to the character of generation Z who choose convenience as the basis for consideration.Suggestion: First, attract Generation Z's Attention by creating engaging and easy-to-digest visual content, such as short videos, infographics, or memes. You can also use their favorite social media platforms. Second, Build Interest by showing the Benefits and Advantages of the campus. Third, Arouse Desire by uploading positive reviews from other customers to build trust and desire. and then provide limited offers or special discounts. Keywords: Marketing Model, AIDA+S, Decision to choose, Generation Z